VD_FINDINFO Jug / 2016 / 447 vom 17. Juni 2016 - VD Tribunal cantonal (2016)
DROIT DE LA FONCTION PUBLIQUE, EMPLOYÉ PUBLIC, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, RÉSILIATION ABUSIVE | 336 CO, 337b CO, 337c CO, 16 LPers-VD, 60 LPers-VD, 61 LPers-VD